Reliability and validity of a wireless microelectromechanicals based system (Keimove™) for measuring vertical jumping performance - Requena, B.; Requena, F.; Garcia, I.; Saez de Villarreal, E.; Pääsuke, M. (Journal of Sports Science & Medicine, 2012)
The aim of this study was to determine the validity and reliability of a microelectromechanicals (MEMs) based system (Keimove™) in measuring flight time and takeoff velocity during a counter-movement jump (CMJ). As criterion reference, data of a high- speed camera (HSC) and a force-platform (FP) synchronized with a linear position transducer (LPT) was used. Thirty professional soccer players completely familiarized with the CMJ technique performed three CMJs. The second and third trials were used for further analysis. The Keimove™ system, the HSC and the FP synchronized with the LPT (FP+LPT) simultaneously measured the CMJ performance. During each repetition, the Keimove™ system registered flight time and velocity at takeoff. At the same time and as criterion reference, both the HSC and the FP recorded the flight time while the LPT+FP registered the velocity at takeoff. Pearson correlation coefficients for the flight time were high (r = 0.99; p < 0.001) when Keimove™ system was compared with the HSC or the FP+LPT, respectively. For the velocity at takeoff variable, the Pearson r between the Keimove™ system and the FP+LPT was lower although significant at the 0.05 level. No significant differences in mean values were observed for flight times and velocity at takeoff between the three devices. Intraclass correlations and coefficients of variation between trials were similar and ranged between 0.92-0.97 and 2.1-7.4, respectively. In conclusion, the Keimove™ system represents a valid and reliable instrument to measure velocity at takeoff and flight time during CMJ testing. Thus, this MEMs-based system will offer a portable, cost-effective tool for the assessment CMJ performance.